The Bad Mood and the Stick - Snicket, Lemony; Forsythe, Matthew 1976- (New York : Little, Brown and Company, 2017)
Curly's bad mood travels from person to person, unexpectedly leaving opportunities for forgiveness, laughter, and love in its wake.
Accelerated Reader AR